The Model for End-Stage Liver Disease Score and the Follow-Up Period Can Cause the Shift of Circulating Lymphocyte Subsets in Liver Transplant Recipients - Pan, Fei; Cao, Shuang; Li, Xian-Liang; Jia, Ya-nan; Wang, Ruo-lin; He, Qiang; Zhu, Ji-Qiao (Frontiers in Medicine, 2022)
Little is known about the shift of lymphocytes under the condition of the model for end-stage liver disease score and the follow-up period. Then, we detected the peripheral blood from liver transplant recipients by flow cytometry and compared the results. The model for end-stage liver disease score affected the percentages of T cell subsets and B cells during the short-term follow-up period but failed to influence the lymphocyte subsets during the long-term follow-up period. In contrast, the follow-up period not only affected the absolute counts of T cell subsets and NK cells in patients with low model for end-stage liver disease scores but also influenced the percentages and absolute counts of T cell subsets in patients with high model for end-stage liver disease scores. In the two-way analysis of variance, we further revealed that the model for end-stage liver disease score was associated with the percentages of T cells and CD4+T cells, and the absolute numbers of T cell subsets and B cells while the follow-up period associated with the percentages of T cell subsets and the absolute numbers of lymphocyte subsets. Therefore, patients with either low model for end-stage liver disease scores or a long-term follow-up period are in a relatively activated immune condition.